O mito de Electra e intertextualidades em O Sonho de Electra, de Bidisha Bandyopadhyay - Prass, Claudiane (2016)
The study presented here focus in reflections and analyses involving the tragedies Electra, by Sophocles; The Libation Bearers, by Aeschylus and Electra, by Euripides, and, based on intertextuality studies this study sought to identify how is Electra s myth is present in the narrative Seahorses, written by the English author of Indian ancestry Bidisha Bandyopadhyayl, published in 1997 in London and translated in Brazil in 1998. The novel Seahorses, still unstudied in Brazil, had a huge impact in the literary milieu, been particularly well received with European press, the author by that time being very young, 17 years old, considered as a prodigy. The myth of Electra contributes on this study due to its importance in recent times, being a study reference for Humanities, besides Literature. This study comprehends a bibliographical research pertaining to the Comparative Literature field, based on the reading of many scholars from diverse areas: literature, anthropology, and even psychiatry. In the perspective of obtaining the aim of the study, we sustained the research in the theoretical assumption recurrent in the study of mythology, studies on the imaginary and intertextuality and for that purposed we relayed on some authors, such as Gilbert Durand, Gaston Bachelard e Jean-Jacques Wunenburger, who shall provide support to the issue of the imaginary. The intertextual discussion among the texts shall be orientated by the study Tiphaine Samoyault and Laurent Jenny. Among other scholars, from mythology studies, literary criticism and even from anthropology and psychiatry, yet it is possible to highlight the scholar Linda Hutcheon in order to contextualize the post-modern novel, Carlinda Pate Nuñez who thoroughly analyzed the three Greek tragedies, as well as Mircea Eliade and E. M. Milietinski. As a result of this investigation process, we understand that the textual upturns, recurring to the literary memory, the text circulates in movements, between what is already given and the new, to the renewed interlacing of the words with other senses and meanings where literature constitutes itself. Henceforth, the myth of Electra is reconsidered, questioned, reviewed, and bringing in itself several other subtleties, issues directly or indirectly related to the myth, in as much the discussion on womanhood and incest.